Additive Nutrition in the Feeding of Pote Goat Madura Maintained the Fertility Post-Infected of Foot and Mouth Disease - Susilowati, Suherni; Lamid, Mirni; Mustofa, Imam; Rosyada, Zulfi Nur Amrina; Agus, Ali; Brahmantya, Chandra; Akintunde, Adeyinka Oye; Hermadi, Herry Agoes; Khairullah, Aswin Rafif; Abuzahra, Mutasem; Ahmad, Riza Zainuddin; Ayuti, Siti Rani (Universitas Airlangga, 2025)
Mineral and nutritive supplements improve animal reproductive performance, especially after Foot and Mouth Disease (FMD) infecteds, to establish sustainable food security solutions. This study aimed to investigate the effects of mineral addition, particularly through premix and concentrate booster supplementation, on the body weight gain and reproductive performance of Pote goats in Madura post-infected of foot and mouth disease (FMD). Thirty-six non-pregnant Pote goats that cured from foot and mouth lesion based on veterinarian examination, were divided into three groups and fed differently for 45 days. Group T0 received standard feed comprising 3-4 kg of forage and 300 g of concentrate with a crude protein content of 16–17%, along with ad libitum water. Groups T1 and T2 received standard feed supplemented with 15g/head/day of premix booster and immune booster, respectively. Results showed no significant increase in body weight with supplementation. However, higher blood urea nitrogen and albumin levels were observed in both T1 and T2-supplemented groups. The estrus rate was higher in goats given mineral supplements than with standard feed alone. Although the onset and duration of estrus did not differ significantly, ultrasound scans showed follicular development before estrus synchronization, indicating restoration of the estrus cycle. Overall, mineral addition in feeding post-FMD infected in Pote goats appears to enhance reproductive performance and overall health.